Pain Following the Use of Anesthesia Formulation Among Individuals Undergoing Cataract Surgery: A Randomized Controlled Trial - Mario D. Toro; Mario D. Toro; Dominika Nowakowska; Agnieszka Brzozowska; Michele Reibaldi; Teresio Avitabile; Claudio Bucolo; Paolo Murabito; Clara Chisari; Katarzyna Nowomiejska; Robert Rejdak (Frontiers Media S.A., 2020)
PurposeTo assess the pain intensity of two intracameral anesthetic solutions in patients undergoing cataract surgery and evaluate the factors influencing the patients' postoperative activities.MethodsSixty-two patients undergoing cataract surgery were randomized to receive the study drug - a manufactured solution of 0.02% tropicamide/0.31% phenylephrine/1% lidocaine (Mydrane) or a traditional anesthetic formulation - solution of 1% lidocaine/0.025% adrenaline as an intraocular anesthetic. The pain intensity was assessed by Visual Analog Scale for Pain (VAS Pain) and Brief Pain Inventory-short form (BPI) on the next day after the surgery.ResultsThe mean pain score measured preoperatively with VAS Pain was 0.34 in Mydrane group and 0.09 in the reference group (p = 0.51). There were no statistically significant differences between the two anesthetic methods with respect to pain intensity during the surgery (p = 0.94) and the influence of pain during the last 24 h on activity (p = 0.79), mood (p = 0.31), social contacts (p = 0.29), sleep (p = 0.5) and the joy of life (p = 0.39). Additionally, there was no statistically significant influence of age, sex, lateralization, co-existing ophthalmological diseases (p = 0.98) and post-operative complications (p = 0.4) on the experienced pain measured during the surgery and in the last 24 h.ConclusionsNew commercially available intraocular anesthetic solution (Mydrane™) seems to be as effective as off-label traditional anesthetic formulation, in reducing the pain experienced during cataract surgery under topical anesthesia.